Analisis Jaringan Trayek Angkutan Umum di Bangkinang Kota Kabupaten Kampar, Riau: Analisis Jaringan Trayek - Tisnawan, Rahmat; Mubarak, Husni; Ramdhani, Fitra; Tambunan, Agustinus (Journal of Infrastructure and Civil Engineering, 2022)
Bangkinang Kota is the capital of kampar which is the center of regional activities such as government, education, economy and so on, so that in this area the usage of vehicles is quite high, especially private vehicles. The amount of private vehicles usage is not comparable to the amount of public transportation available. Therefore, the aim of this study wants to plan a new public transportation in the city center by connecting the surrounding areas. Public transportation planning is carried out by calculating the amount of demand for public transportation, then the results of the demand calculation are used as a reference for determining the route system. Before calculating the demand and determining the route system, the first step is collecting primary and secondary data, then analyze a demand in the form of trip generation, distribution of trip and mode selection. Furthermore, from the demand analysis, there are 3 (three) public transport routes who serve Bangkinang Kota.